Inclusive Approaches in Italian Early Childhood Education and Care: The View of Practitioners - Alessia Macagno; Beatrice Ragaglia; Anne Henning; Daniela Bulgarelli (MDPI AG, 2024)
This study presents the Italian practitioners' perspective on the inclusion of children with disabilities in ECEC. Historically, Italy had a split system (0-3 and 3-6 divisions); only recently was the ZeroSix Integrated System established. Seven 0-3-division educators and seven 3-6-division teachers were interviewed. Their responses were analysed through a deductive content analysis, based on the eight dimensions of inclusion proposed by the European Agency for Special Needs and Inclusive Education (2017). The themes which were mainly mentioned as crucial for promoting inclusion were a child-centred approach; inclusive teaching and learning environment; inclusive social environment; and family-friendly environment. These same dimensions were also said to be challenging, together with the implementation of materials for all children. The strengths and weaknesses in inclusive processes partly differed between the two divisions. This study enriches the literature investigating how practitioners implement inclusive practices in ECEC, also analysing the differences between the 0-3 and the 3-6 divisions.